2015
DOI: 10.3141/2526-02
|View full text |Cite
|
Sign up to set email alerts
|

Validating Rail Transit Assignment Models with Cluster Analysis and Automatic Fare Collection Data

Abstract: Passenger flow data are necessary for making and coordinating operational plans for urban rail transit (URT) systems; the availability and the service state of those systems directly influence the activity of a city and its people. Although many transit assignment models have been developed, the results of passenger flows estimated by these models as well as assumptions made in the estimation process, especially for large-scale, complex, and dynamically changing URT networks, had not been validated. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The clustering approach adopted here is based on the fact that cluster centers are characterized by a higher density than their neighbors and by a relatively large distance from the points with higher densities [17,18]. For each data point , we compute two quantities: local density and the distance from the points with higher density.…”
Section: Cluster Analysis Algorithmmentioning
confidence: 99%
“…The clustering approach adopted here is based on the fact that cluster centers are characterized by a higher density than their neighbors and by a relatively large distance from the points with higher densities [17,18]. For each data point , we compute two quantities: local density and the distance from the points with higher density.…”
Section: Cluster Analysis Algorithmmentioning
confidence: 99%
“…To validate existing metro flow assignment models, Zhu et al. () further developed a methodology based on automatic fare collection data and a cluster analysis technique. It is found that the accuracy of flow assignment depends on whether travel cost and transferring cost can be determined accurately.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Path candidates for each origin-destination pair are first generated, and the proposed calibration method subsequently assigns the detailed passenger flow over the metro network. To validate existing metro flow assignment models, Zhu et al (2015) further developed a methodology based on automatic fare collection data and a cluster analysis technique. It is found that the accuracy of flow assignment depends on whether travel cost and transferring cost can be determined accurately.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, many transit assignment models have been proposed, and comprehensive reviews have been presented in the literature (Oliker and Bekhor, 2018;Yao et al, 2017;Patriksson, 2015;Saw et al, 2014;Imran and Matthews, 2015). Over time, researchers and experts have acknowledged that these models must be validated, especially for those largescale and multimodal transit networks (Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Agard et al, 2013;Asakura et al, 2012;Kusakabe and Asakura, 2014;Zhao et al, 2017a), journey time reliability(Uniman et al, 2010;Rahbar et al, 2017;Bagherian et al, 2016;Ma et al, 2017b), trip purposes(Lee and Hickman, 2014b;Trépanier et al, 2007;Long and Thill, 2015;Lee and Hickman, 2014a), passenger flow on different routesRahbar et al, 2017;Zhu et al, 2014;Zhu et al, 2015;Zhu et al, 2017), etc Pelletier et al (2011b). present a comprehensive review of uses of smart card…”
mentioning
confidence: 99%